A bran-new equivalent orthotropic-plate method for nonlinear bending of combined double bottom structure with variable stiffness. (1st February 2023) - Yu, Qiang; Xu, Hang
Abstract: A bran-new equivalent orthotropic-plate method is developed for analysis of double-bottom hull structure constituted by double panels orthogonally assembled with girders and webs, while the bending properties with non-uniformity of sandwiched height are characterized and approximated by equivalent variable-stiffness. Two mechanical models of mutual interaction considering the continuity of membrane stress or strain are investigated respectively with uniformly distributed membrane stress along the thickness direction or strain equalization at the interface of panels and sandwiched grillage frame. Geometrically nonlinear bending analysis of the structure has been studied based on the large-deflection orthotropic plate theory, while the solutions obtained by a wavelet-based homotopy approach have been verified in satisfactory accuracy with published benchmark. Applicability of the equivalent orthotropic-plate model has been assessed by predicting the global bending in good accordance with FEM results, which validates its superiority in demonstrating the features of nonlinear deformed characteristics. The influence of structural orthotropy on bending properties of double bottom has been investigated, which is of great significance on overall deflection and orthogonal discrepancy of resultant bending moments, as both greatly affected in large orthotropic ratios at linear and nonlinear bending stages.